Regional Climate Simulation for Arizona: Impact of Resolution on Precipitation - Ashish Sharma; Huei-Ping Huang (Advances in Meteorology)
This study performs regional climate simulations for Arizona, a region with complicated terrain. The dependence of simulated rainfall on model resolution is explore by climate downscaling experiments using the Weather Research and Forecasting model. The model’s horizontal resolution was refined from 12 to 6, then to 3 km. The total rainfall for winter and for different subdomains of Arizona is found to increase substantially with the refinement from 12 to 6 km grid. A further refinement to 3 km leads to a smaller change in rainfall, indicating numerical convergence at that scale. Comparisons with observations revealed that the 6 and 3 km runs produced excessive rainfall for winter while the 12 km simulations are closer to observation. This implies that the parameterization schemes for rainfall are not resolution independent, thus a refinement of resolution does not guarantee better results. It cautions against hastily pushing for increasingly higher resolution in practical downscaling simulations. An analysis of the simulated hourly rainfall shows that the 3 km runs produce significantly more extreme rainfall events than the 12 km runs. The 6 and 3 km runs also produced more complicated spatial patterns of seasonal rainfall and vertical velocity, reflecting the influence of fine-scale topography.